(untitled) (REMUNOM, 2026)
Introduction: Autism Spectrum Disorder (ASD) encompasses a variety of impairments in skills that lead to deficits in communication, social interaction, and behavioral changes, with little or no verbal communication and a specific repetitive pattern. Objective: To analyze, based on the scientific literature, the perceptions of parents of children with Autism Spectrum Disorder regarding health care practices. Methodology: This is an integrative literature review study conducted using articles published in the following databases: LILACS (Latin American Literature in Health Sciences), Google Scholar, Web of Science, Scopus, and SciELO (Scientific Electronic Library Online). The search was performed using the Health Sciences Descriptors (DeCS): "Autism Spectrum Disorder"; "Health care"; "Parents"; and "Nursing care". The inclusion criteria used were review studies and field research (primary), published in Portuguese, English, and Spanish; between 2020 and 2025; available in open access and in full text. Exclusion criteria included: editorials; books and book chapters; theses; dissertations and monographs, as well as duplicate articles in the databases. Results: 1,248 articles were identified. After applying the inclusion and exclusion criteria and extensive reading, a final sample of eight articles related to the theme of parental perceptions in the health care of children with Autism Spectrum Disorder was obtained. Discussion: Problems such as long waiting lists, late diagnoses, inefficient communication, unprepared professionals, and waiting rooms with excessive stimuli are some of the many examples that permeate the negative experience of parents. Conclusion: The study was able to observe different parental perceptions, providing a broader perspective on how assistance is offered within the Psychosocial Care Network (RAPS) for atypical children, highlighting gaps and the emergence of new strategies to address and reverse them.